(untitled) (Journal of Fatwa Management and Research, 2018)
This paper aims to discuss the jurisprudence dilemmas of the Takaful surplus in the Takaful companies from two aspects: the contractual relationship between the subscribers and the solidarity-fund, and the contractual relationship between the company and solidarity-fund. Based on the contracts formulas that applied in the Takaful companies, one can know the way that these companies follow to disposing the Takaful surplus, and the extent that these companies have right to deduce the proportion from the surplus as motivation for its good governance of solidarity- fund. By inducing the legitimacy (Islamic) standards and the jurisprudential academies views about the Takaful surplus, following and analyzing these views, the researcher will try to reach to resolve the outstanding jurisprudential issues in consistent with the legitimacy (Islamic) standards and Islamic purposes. Keywords: Takaful Surplus, Solidarity fund, Contractual relationship, Legitimacy (Islamic) standards. الملخّص تهدف هذه الورقة إلى مناقشة الإشكالات الفقهية حول الفائض التأميني بشركات التكافل, وذلك من جانبين: جانب العلاقة التعاقدية بين المشتركين والصندوق التكافلي, وجانب العلاقة التعاقدية بين الشركة والصندوق التكافلي. فمن خلال النظر إلى صيغ العقود المطبقة بشركات التكافل يمكن معرفة الكيفية المتبعة للتصرف بالفائض التأميني, ومدى أحقية الشركة في اقتطاع نسبة من الفائض كحافز عن حسن إدارتها للصندوق التكافلي, وباستقراء المعايير الشرعية, وآراء المجامع الفقهية حول مسألة الفائض التأميني, وتتبع الآراء الفقهية وتحليلها؛ سيتوصل الباحث بعونه تعالى لحلحلة المسائل الفقهية العالقة بما يتفق مع الضوابط الشرعية, ومقاصد الشريعة الإسلامية.